Market institutions in sub-Saharan Africa: Theory and evidence - Fafchamps, M (MIT Press, 2004)
Summarizes a decade of the author's empirical and theoretical work aimed at understanding market institutions in sub-Saharan Africa. Addresses issues of contract enforcement; trust and relationships; information sharing; networks and markets; and ethnicity and discrimination. Draws on a series of panel surveys of manufacturing firms in Burundi, Cameroon, Ivory Coast, Ghana, Ethiopia, Kenya, Tanzania, Zambia, and Zimbabwe; complementary case studies of manufacturing and trading firms in Ghana, Kenya, and Zimbabwe; and surveys of agricultural traders in Benin, Madagascar, and Malawi. Considers policy implications. Fafchamps is Reader in the Department of Economics and Professorial Fellow at Mansfield College, Oxford University. Bibliography; index.